Pengaruh Lingkungan Kerja dan Kompetensi Kerja terhadap Kinerja Pegawai - Dimas Maulana Rifqy; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
ABSTRACK. The research that the author makes has the aims of:1) Exploring the analysis of the work environment at the Daarut Tauhiid Foundation. 2) Analyze the work competence of the Daarut Tauhiid Foundation. 3) Analyze the performance of employees at the Daarut Tauhiid Foundation. 4) Analyze the influence of the work environment on employee performance at the Daarut Tauhiid Foundation, Bandung. 5) Analyze the effect of job satisfaction on employee performance at the Daarut Tauhiid Foundation, Bandung. 6) Analyze the influence of the work environment and job satisfaction on employee performance at the Daarut Tauhiid Foundation, Bandung. The type that the author uses in this research is a quantitative research type in which descriptive and verification analysis methods are used for the description. The calculation operation is to use the SPSS 25.0 program. In this study, there are several variables, namely: Work Environment, Work Competence, and Employee Performance. The data obtained by the authors were collected through questionnaires that the authors distributed, documentation, and through library research. Sampling in this study used a saturated sampling technique. In this study, the respondents that the author got came from employees of the Daarut Tauhid Foundation in Bandung, amounting to 60 people. This research has the result that: work environment of employees at the Daarut Tauhiid Foundation in Bandung is in the sufficient category. 2) Work Competence of employees at the Daarut Tauhiid Foundation in Bandung is in the sufficient category. 3) The performance of employees at the Daarut Tauhiid Foundation in Bandung is in the sufficient category. 4) The work environment if seen in this partial has a significant influence on the work performance of the officers at the Daarut Tauhiid Foundation in Bandung. 5) The performance competence possessed by officers partially has a significant influence on the work performance of officers at the Daarut Tauhiid Foundation, Bandung. 6) Work Environment and Work Competence according to which simultaneously have a significant influence on employee performance at the Daarut Tauhiid Foundation Bandung. Abstrak. Penelitian yang penulis buat memiliki tujuan untuk: 1) Mengulik analisis pada lingkungan kerja di Yayasan Daarut Tauhiid. 2) Menganalisis kompetensi kerja pada Yayasan Daarut Tauhiid. 3) Menganalisis kinerja pegawai pada Yayasan Daarut Tauhiid. 4) Menganalisis pengaruh Lingkungan Kerja terhadap Kinerja Pegawai pada Yayasan Daarut Tauhiid Bandung. 5) Menganalisis pengaruh Kepuasan Kerja terhadap Kinerja Pegawai pada Yayasan Daarut Tauhiid Bandung. 6) Menganalisis pengaruh Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai pada Yayasan Daarut Tauhiid Bandung. Jenis yang penulis pakai pada penelitian ini ialah jenis penelitian kuantitatif yang didalamnya dipakai metode analisis deskriptif serta verivikatif untuk penjabarannya. Pengoperasian hitungannya ialah dengan memakai program SPSS 25.0. dalam penelitian ini terdapat beberapa variable, yakni: Lingkungan Kerja, Kompetensi Kerja, serta Kinerja pada diri Pegawai. Data yang didapat penulis kumpulkan lewat kuesioner yang penulis bagikan, dokumentasi, serta melalui studi pustaka. Penarikan sample dalam penelitian ini menggunakan teknik sampling jenuh. Dalam penelitian ini, responden yang penulis dapatkan berasal dari Pegawai Yayasan Daarut Tauhid Bandung yang berjumlah 60 orang. Penelitian ini memiliki hasil bahwasanya: Lingkungan Kerja pegawai di Yayasan Daarut Tauhiid bandung termasuk kategori cukup. 2) Kompetensi Kerja pegawai di Yayasan Daarut Tauhiid Bandung termasuk kategori cukup. 3) Kinerja pegawai di Yayasann Daarut Tauhiid Bandung termasuk kategori cukup. 4) Lingkungan Kerja jika dilihat dalam parsial ini memiliki pengaruh yang signifikan pada prestasi kerja para petugas di Yayasan Daarut Tauhiid Bandung. 5) Kompetensi kinerja yang dimiliki oleh petugas secara parsial memiliki pengaruh yang signifikan pada prestasi kerja petugas di Yayasan Daarut Tauhiid Bandung. 6) Lingkungan Kerja serta Kompetensi Kerja yang menurut simultan memiliki pengaruh yang signifikan pada prestasi kerja pegawai di Yayasan Daarut Tauhiid Bandung.